Leukemia Recurrence Exclusively in the Breast after Stem Cell Transplant. Issue 1 (15th August 2018) - Samreen, Naziya; Hashmi, Shahrukh K.; Conners, Amy Lynn; Bhatt, Asha; Glazebrook, Katrina N.
Introduction: Leukemic involvement of the breast is extremely rare but constitutes an oncologic emergency. Imaging findings of T-Cell acute lymphoblastic leukemia (T-ALL) recurrence in the breasts have not been previously described. Case Description: Patient is a 25 year old female who presented with symptoms of superior vena cava (SVC) obstruction secondary to a mediastinal mass status post biopsy demonstrating T-ALL, which was cluster of differentiation 3 (CD3) positive and B-cell lymphoma 2 (BCL-2), and 80% Ki-67 positive. She was treated with chemotherapy and post-treatment positron emission tomography/computed tomography (PET/CT) demonstrated resolution of mediastinal mass, with no evidence of distant disease. She underwent allogeneic hematopoietic stem cell transplant (HSCT) in first remission. Seven months post-HSCT, patient presented with a large area of tender swelling of both the breasts with biopsy demonstrating relapsed T-ALL. Radiologic findings showed bilateral breast masses on ultrasound and mammogram, which were hypermetabolic on PET/CT. Conclusions: Breast involvement in leukemia recurrence, a very rare entity, can present with palpable masses. Mammographic findings in leukemia can include masses or architectural distortion, they are typically hyperechoic on ultrasound, and can have marked uptake on PET/CT. Oncologists, primary care providers and radiologists should be aware of leukemia presentations in the breast for prompt referral for urgent management.